A broad-band perspective on circular polarization in radio pulsar observations. Issue Volume 16:Issue S363(2020) (June 2020) - Oswald, Lucy S.
Abstract: We investigate the broad-band behaviour of circular polarization in radio pulsar profiles and show the relationship between polarization fraction and what proportion of that polarization is circular, both across frequency, and for a large number of pulsars viewed collectively. The behaviour observed may be explained by pulsar polarization originating from the partially-coherent combination of two linearly-polarized orthogonal modes with different flux spectral indices. (See also the poster in the "supplementary information".)